Early Surfactant Therapy With Nasal Continuous Positive Airway Pressure or Continued Mechanical Ventilation in Very Low Birth Weight Neonates With Respiratory Distress Syndrome - Najafian, Bita (Kowsar, 2014)
BACKGROUND: Various strategies have been suggested for the treatment of respiratory distress syndrome (RDS). OBJECTIVES: The aim of this study was to compare the efficacies of two common methods of RDS management among neonates with low birth weight. PATIENTS AND METHODS: A cohort study was conducted on 98 neonates with definite diagnosis of RDS during 2008-2009. The neonates were divided into two groups by a blinded supervisor using simple randomization (odd and even numbers). Forty-five cases in the first group were treated with intubation, surfactant therapy, extubation (INSURE method) followed by nasal continuous positive airway pressure (N.CPAP) and 53 cases in the second group underwent intubation, surfactant therapy followed by mechanical ventilation (MV). RESULTS: Five (11.1%) cases in the first group and 23 (43%) cases in the second group expired during the study. The rates of MV dependency among cases with INSURE failure and cases in the MV group were 37% and 83%, respectively (P < 0.001). Birth weight (BW) (P = 0.017), presence of retinopathy of prematurity (P = 0.022), C/S delivery (P = 0.029) and presence of lung bleeding (P = 0.010) could significantly predict mortality in the second group, although only BW (P = 0.029) had a significant impact on the mortality rate in the first group. Moreover, BW was significantly related to the success rate in the first group (P = 0.001). CONCLUSIONS: Our findings demonstrated that INSURE plus NCPAP was more effective than the routine method (permanent intubation after surfactant prescription). In addition, the lower rates of mortality, MV dependency, duration of hospitalization, and complications were observed in cases treated with the INSURE method compared to the routine one.